Pengalaman Traumatis Sebagai Penyebab Gangguan Jiwa Psikotik Akut - Aviva Sintia Emira; Afrina Zulaikha (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
A traumatic experience is an incident or occurrence that shakes the soul, related to physical injuries or violence that a person has experienced. This condition can trigger stress and even trauma in individuals who experience this in the future. The response to this traumatic experience in some cases can continue for a longer period of time and interfere with daily life due to a neurotransmitter imbalance where a person continues to remember the event. This carries the risk of developing a psychotic disorder.